Effect of smear layer thickness and pH of self-adhesive resin cements on the shear bond strength to dentin - Mohammad Esmaeel Ebrahimi Chaharom; Amir Ahmad Ajami; Mahmoud Bahari; Haleh Rezazadeh (Wolters Kluwer Medknow Publications, 2017)
Context: There are concerns in relation to the bonding efficacy of self-adhesive resin cements to dentin covered with the smear layer. Aims: This study aims to evaluate the effect of smear layer thickness and different pH values of self-adhesive resin cements on the shear bond strength to dentin. Materials and Methods: The dentin on the buccal and lingual surfaces of 48 sound human premolars were abraded with 60- and 600-grit silicon carbide papers to achieve thick and thin smear layers, respectively. The samples were divided into three groups (n = 16) based on the cement pH: Rely-X Unicem (RXU) (pH < 2); Clearfil SA Luting (CSL) (pH = 3); and Speed CEM (SPC) (pH = 4.5). In each group, composite resin blocks were bonded to the buccal and lingual surfaces. After 24 h, the shear bond strength values were measured in MPa, and the failure modes were evaluated under a stereomicroscope. Statistical Analysis: Data were analyzed with two-way ANOVA and post hoc least significant difference tests (P < 0.05). Results: Cement pH had a significant effect on the shear bond strength (P = 0.02); however, the smear layer thickness had no significant effect on the shear bond strength (P > 0.05). The cumulative effect of these variables was not significant, either (P = 0.11). Conclusion: The shear bond strengths of SPC and CSL self-adhesive resin cements were similar and significantly lower than that of RXU. The smear layer thickness was not a determining factor for the shear bond strength value of self-adhesive resin cements.